In vivo evaluation of the anticancer activity of the gemcitabine and doxorubicin combined in a nanoemulsion - Mayson H Alkhatib; Wafa S Alshehri; Faiza B Abdu (Wolters Kluwer Medknow Publications, 2018)
Context: Doxorubicin (DOX) and gemcitabine (GEM) are anticancer drugs that were combined in a nanoemulsion (NE) to reduce their adverse side effects. Aim: To detect the antitumor activity of the combination formulas of GEM and DOX, loaded either in water (GEM+DOX-Sol) or in NEs (GEM-DOX combination/loaded NE [GEM+DOX/LNE]), in female Swiss albino mice inoculated with Ehrlich ascites carcinoma (EAC). Settings and Design: The anticancer assessment of the NE formulas was implemented in 200 mice, which were divided into 10 groups. Materials and Methods: It includes the detection of the change in body weight, analysis of the hematological and serum biochemical profiles, and study of the histopathologic alterations of the heart tissues. Statistical Analysis: One-factor analysis of variance was used. Results: Mice treated with GEM + DOX/LNE, which have an z-average of 155.38±2.33nm and zeta potential of −38.5±1.3 mV, recorded a considerable improvement in the mean survival time (MST), which was 60 days, as compared to the EAC control group, which has an MST of 28 days. It also restored the hematological and serum biochemical parameters toward normal values. Conclusions: The combination of GEM and DOX in NE has significantly diminished the cardiotoxicity of DOX and hematotoxicity of GEM while improving their antitumor properties.